Mengoptimalkan Pola Pikir Filsafat dan Islam di Kalangan Mahasiswa dan Dosen (Studi di Prodi Aqidah dan Filsafat Islam, UIN Sumatera Utara) - Bahri, Fajar Nur; Adenan, Adenan; Andhara, Andhara (UIN Sumatera Utara, 2025)
This study examines efforts to optimize an integrative mindset of philosophy and Islamic values among students and lecturers in the Aqidah and Islamic Philosophy Study Program at the Faculty of Ushuluddin and Islamic Studies, UIN Sumatera Utara. Employing a mixed-methods design, the research combines a phenomenological qualitative approach to capture participants' subjective perspectives and quantitative analysis using descriptive and inferential statistics on a stratified random sample of sixteen respondents. Data were gathered via semi-structured interviews, Likert-scale questionnaires, and classroom observations, then subjected to thematic analysis and triangulation for enhanced validity. Key findings reveal that students exhibit adaptive and creative thinking patterns, while lecturers adopt reflective and strategic mindsets. Both internal factors (motivation, belief systems, educational background) and external factors (curriculum design, teaching methods, academic environment) influence the development of an integrative mindset. Optimization strategies include strengthening literacy and open discussions, collaborative social projects, curriculum revision with contemporary case studies, and positioning lecturers as intellectual and spiritual facilitators. The study concludes that although critical and integrative thinking skills have emerged, challenges such as rote learning habits, limited discussion spaces, and personal hesitations remain and must be addressed through strategic interventions to harmonize reason and revelation in Islamic academic contexts.